Kin affiliation, socio-sexual and mating preference in the female Microtus ochrogaster in a multiple socio-sexual preference test - Ferreira-Nuño, Armando; Young, Larry J.; Morales Otal, Adriana; Camacho, Francisco; Díaz, Néstor F.; Paredes, Raúl G.; Prado, Alberto; Cruz Benites, Antonio; Portillo, Wendy (Frontiers in Ecology and Evolution, 2023)
Introduction The prairie vole (Microtus ochrogaster) is a socially monogamous species that, after cohabitation with mating, forms an enduring pair bond. It has been suggested that female prairie voles avoid mating with fathers and siblings to prevent inbreeding depression. However, controlled laboratory tests of preferences involving males with varying degree of relatedness have not been conducted. Methods To address this, we employed a multiple socio-sexual preference arena consisting of four adjacent cylinders arranged in a closed circle. In each cylinder, we placed a male of varying relatedness to the experimental female (i.e., father, sibling, first-degree cousin, and unrelated males) and registered their behavior for five hours. Male socio-sexual preference was determined by the proportion of time spent in each male's chamber, which can be driven by affiliative preferences for the father and sibling and sexual attraction for the cousin and unrelated males. Mating preference was analyzed as the frequency of mating with each male. We hypothesized that receptive females would show sexual attraction and mating preferences for the unrelated males and cousins and affiliative preferences for the fathers and siblings. Results Our analyses showed that females spent more time with first-degree cousins and mated more often with them compared to unrelated males, siblings, or fathers. However, complete inbreeding avoidance was not observed, and some females mated with siblings, fathers, or both. Discussion Although our results did not support the hypothesis, they are consistent with other studies that have argued that mating with first-degree cousins optimizes the costs and benefits associated with inbreeding and outbreeding.